ANALISIS KEBUTUHAN KURIKULUM MUATAN LOKAL BERBASIS BUDAYA DAERAH DALAM PENGEMBANGAN PENDIDIKAN KARAKTER PADA SISWA SD - Supeni, Siti; Yusuf, Yusuf; Oktavia, Bella Nur (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
The purpose of the study is to: (1) analyze the needs of a local content curriculum (Mulok) based on regional culture in the development of character education in elementary school students in 2021 in the city of Surakarta. (2) make procedures for developing local content curricula based on regional culture. (3) testing the effectiveness of the regional culture-based local content curriculum (Mulok) in the development of character education in elementary school students in 2021 in the city of Surakarta. (3) Draft a guidebook for the local Content Curriculum (Mulok) based on regional culture in the development of character education in elementary school students in 2021 in the city of Surakarta for use in elementary schools in Surakarta, seen from educational, creative, and competitive aspects. Research methods through literature studies, interviews, surveys, observations, and documentation. Qualitative descriptive data analysis. About the local content curriculum (Mulok) based on regional culture in the development of character education in S D studentsin Surakarta, supported through psychological, educational, and socio-cultural approaches. The findings: (1) identification of various regional cultural activities in schools; benefits and objectives, materials used, and technical activities, (2) identification of local Content Curriculum figures; various regional cultural activities, (3) formulate character education based on regional culture